Liquid crystalline polymer nanocomposites reinforced with in-situ reduced graphene oxide - D. Pedrazzoli; A. Dorigato; T. Conti; L. Vanzetti; M. Bersani; A. Pegoretti (eXPRESS Polymer Letters)
In this work liquid-crystalline polymer (LCP) nanocomposites reinforced with in-situ reduced graphene oxide are investigated. Graphene oxide (GO) was first synthesized by the Hummers method, and the kinetics of its thermal reduction was assessed. GO layers were then homogeneously dispersed in a thermotropic liquid crystalline polymer matrix (Vectran®), and an in-situ thermal reduction of GO into reduced graphene oxide (rGO) was performed. Even at low rGO amount, the resulting nanocomposites exhibited an enhancement of both the mechanical properties and the thermal stability. Improvements of the creep stability and of the thermo-mechanical behavior were also observed upon nanofiller incorporation. Furthermore, in-situ thermal reduction of the insulating GO into the more electrically conductive rGO led to an important surface resistivity decrease in the nanofilled samples.